Beyond the ripples - Montgomery, Dede (Bink Books, Bedazzled Ink Publishing Company, 2019)
How might a small decision you make, an action you take, a phone call you initiate change your path? Impact other lives? Months after spying a bottle wedged into a fallen cottonwood snag in the Columbia River, Ernest pulls it from the river. The bottle<U+2019>s note connects Ernest, an old man living in a tiny Oregon town, to teenage Annie, provoking a mysterious and sudden friendship between Ernest<U+2019>s daughter Amelia with Sarah, the daughter of the most recent resident of the home Annie once occupied. The two middle-aged women<U+2019>s quest to learn more about Annie and her secret introduces readers to stories about family members through backstory, and introduces new characters, all connected through the finding of the bottle. Together, Amelia and Sarah explore their unfinished business with their mothers, intimate relationships, and regrets over life choices as they embark on their personal searches for something bigger in their very different lives.